2021
DOI: 10.1002/admi.202100333
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mineralization: Low‐Temperature, Rapid, and Multidirectional Process to Encapsulate Polyether‐Ether‐Ketone with Carbonate‐Rich Hydroxyapatite for Osseointegration

Abstract: Polyether‐ether‐ketone (PEEK) is one of the key materials used to fabricate intervertebral spacers due to its mechanical similarity to bone and non‐interference with imaging. However, its surface chemistry limits osseointegration, while its chemical unreactivity and low glass transition/melting temperature poses technical challenges to the application of coatings conducive to bone growth. The present work applies nature‐inspired interfacial and surface chemistry processes to encapsulate PEEK with nanocrystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 74 publications
(94 reference statements)
1
11
0
Order By: Relevance
“…The thickness of the microcoating is driven by the low-temperature deposition process, where a precursor CaCO 3 -NP microcoating is deposited onto an exposed area of a glass slide by the CSA technique and subsequently converted to carbonate-rich hydroxyapatite through dissolution-recrystallization processes in PBS. [18] The CSA technique induces the self-assembly of CaCO 3 -NPs toward the triple contact line of liquid (CaCO 3 -NP suspension), solid (glass), and vapor phase (air) due to capillary forces at the meniscus when the suspension evaporates. [24,25] The contact angle is a key determinant of deposition thickness [18,24,25] and previous studies that used a similar low-temperature deposition method to deposit a contiguous microfilm of carbonate-rich hydroxyapatite on polyether-ether-ketone (PEEK) reported a film thickness of <3 µm.…”
Section: Thicknessmentioning
confidence: 99%
See 3 more Smart Citations
“…The thickness of the microcoating is driven by the low-temperature deposition process, where a precursor CaCO 3 -NP microcoating is deposited onto an exposed area of a glass slide by the CSA technique and subsequently converted to carbonate-rich hydroxyapatite through dissolution-recrystallization processes in PBS. [18] The CSA technique induces the self-assembly of CaCO 3 -NPs toward the triple contact line of liquid (CaCO 3 -NP suspension), solid (glass), and vapor phase (air) due to capillary forces at the meniscus when the suspension evaporates. [24,25] The contact angle is a key determinant of deposition thickness [18,24,25] and previous studies that used a similar low-temperature deposition method to deposit a contiguous microfilm of carbonate-rich hydroxyapatite on polyether-ether-ketone (PEEK) reported a film thickness of <3 µm.…”
Section: Thicknessmentioning
confidence: 99%
“…[18] The CSA technique induces the self-assembly of CaCO 3 -NPs toward the triple contact line of liquid (CaCO 3 -NP suspension), solid (glass), and vapor phase (air) due to capillary forces at the meniscus when the suspension evaporates. [24,25] The contact angle is a key determinant of deposition thickness [18,24,25] and previous studies that used a similar low-temperature deposition method to deposit a contiguous microfilm of carbonate-rich hydroxyapatite on polyether-ether-ketone (PEEK) reported a film thickness of <3 µm. [18] In addition to substrate type (PEEK vs. glass), other factors that may have contributed to the differences in thickness include temperature (130 • C vs. 80 • C), angle at which the sample was placed in the suspension, and the presence of the polypropylene-based tape that surrounds the exposed area of the glass slide.…”
Section: Thicknessmentioning
confidence: 99%
See 2 more Smart Citations
“…For solving this problem, many methods to impart bioactivity to the PEEK have been reported [10]. For example, titanium oxide (TiO 2 ) coating by the sol-gel process [11,12], sulfuric acid (H 2 SO 4 ) treatment [13], H 2 SO 4 and calcium chloride (CaCl 2 ) treatment [14], and carbonate-rich hydroxyapatite coating by dynamic mineralization [15] have been reported. In addition, Prochor et al reported that PEEK reinforced with 30% glass fiber showed hydroxyapatite formation [16].…”
Section: Introductionmentioning
confidence: 99%